Modelisation of chloride reactive transport in concrete including thermodynamic equilibrium, kinetic control and surface complexation. (August 2018) - Tran, Van Quan; Soive, Anthony; Baroghel-Bouny, Véronique
Abstract: In this study, a new physically and chemically based model taking into account thermodynamic equilibrium, kinetics and surface complexation is proposed to predict the ingress of chloride ions into saturated concretes. The numerical results of this multi-ionic model are compared to experimental data such as total and free chloride concentration profiles and chloride binding isotherms. With only one set of parameters, the results show very good agreement for chloride binding isotherm of concretes with different w / b, types of binders (CEM I, CEM III, and CEM I with fly ash) and various exposure conditions (NaCl solution at different concentrations). Such a model overcomes the use of empirical chloride binding isotherms that can be difficult to asses for concretes with supplementary cementitious materials. The very good results underline the need to take into account all the physical and chemical phenomena included in the model.